Simultaneous design and control of an industrial two-stage mixed suspension mixed product removal crystallizer. (August 2019) - Porru, Marcella; Özkan, Leyla
Highlights: The integrated design and control problem of industrial series of MSMPR crystallizers is studied simultaneously. An optimization approach with a cost function consisting of equipment and utility costs, average crystal dimension as product quality and dynamic operability, is used to find the best configuration. Several control schemes based on combination of prediction and feedback elements are studied to address the inherent input-output delay. The performance of various controller designs is assessed in simulation in the case of noise free and noisy measurements. Abstract: This work is motivated by the renewed interest in continuous crystallization processes as an alternative to batch crystallizers, and studies the simultaneous design and control of industrial two stage mixed suspension mixed product removal crystallizers. To this end, we optimize concurrently process economics, product quality criteria as well as process controllability, which are often conflicting objectives. The optimal configuration is found by solving a multi-objective, steady state and constrained optimization problem that requires the knowledge of the process model, capital costs as a function of the decision variables, and the pairing of the control variables. Subsequently, various controllers are tailored on the optimal configuration to guarantee consistent average crystal dimension of the product under disturbances. Traditional feedback (proportional integral PI) controllers result in sluggish closed loop performance with no offset. The performance is improved by delay compensation control schemes or feedforward-feedback combinations, which are able to cope with the inherent time delays of the industrial process, and tested with noise-free and noisy measurements.